Making the mouse embryo transparent: identifying developmental malformations using magnetic resonance imaging. - Schneider, J; Bhattacharya, S (2004)
Developmental malformations are a major cause of childhood mortality and are typically characterized by lesions that allow survival of the embryo through gestation. The genetics of developmental malformations are powerfully studied by using high-throughput, phenotype-driven screens (e.g., following zebrafish or mouse mutagenesis) or by genotype-driven studies using transgenic or knockout mice. With regard to either approach, the mouse is anatomically and phylogenetically closer to humans than any other genetically tractable model organism. This is particularly important in the cardiovascular and respiratory systems, which have unique mammalian features. The identification of murine models of developmental malformations is, however, hindered by the opacity of the late gestational mouse embryo. In this review, we describe recent advances in magnetic resonance imaging that make it possible to rapidly identify malformations in the developing mouse embryo with high efficiency.